3D printing of composite noise barrier sandwich structure - Neo, Casper Song Jiang (Nanyang Technological University, 2020)
Land scarcity and population growth issues have indirectly amplified noise pollution, which has caused physiological, psychological and health problems. The report deals with noise pollution by providing an alternative material and design concept. Problems with conventional manufacturing techniques of fabricating noise barriers are the lack of flexibility of creating intricate parts, and a limited variety of material. On the other hand, additive manufacturing technique does not have these problems. In this report, equipment like Microhardness Tester FM–300e, Quasi – Static Indentation, Bruker SKYSCAN 1173, PULSE Acoustic Material Testing Machine was used to perform an in-depth analysis of alternative material and design concept of a noise barrier. Quasi – Static Indentation analyses conducted on the various layups determined that bi – directional fiberglass layup has the greatest absorption which far exceed many others in the same material or layup. With the implementation of bi – directional layup on sandwich cores, hybrid honeycomb sandwich structure proves to have the highest total energy per unit mass of 615.4 J/Kg that can withhold greater compressive force when needed in a structural application as there is a possibility that noise barrier may require to resist vehicular impact as it requires a certain structural integrity to hold the shape and sandwich structure. PULSE Acoustic Material Testing Machine was used to determine respective absorption coefficient and reduction in sound pressure level (SPL). In exploration of acoustic properties with various air gap ratio between 50 ~ 70 %, concluded a limit between the ratio of air gap and material. Analyses determined that HHSC – BDF which has an air gap of 60 % has the highest reduction in SPL of 28 % that reduces harmful sounds to a safe sound level.